Topoisomerase IV tracks behind the replication fork and the SeqA complex during DNA replication in Escherichia coli - Helgesen, Emily; Sætre, Frank; Skarstad, Kirsten (Scientific reports, 2021)
Topoisomerase IV (TopoIV) is a vital bacterial enzyme which disentangles newly replicated DNA and enables segregation of daughter chromosomes. In bacteria, DNA replication and segregation are concurrent processes. This means that TopoIV must continually remove inter-DNA linkages during replication. There exists a short time lag of about 10–20 min between replication and segregation in which the daughter chromosomes are intertwined. Exactly where TopoIV binds during the cell cycle has been the subject of much debate. We show here that TopoIV localizes to the origin proximal side of the fork trailing protein SeqA and follows the movement pattern of the replication machinery in the cell.